Optimization of The Use of Togaf Adm in The Design of Information Systems For Islamic Boarding Schools - Nurliana Nasution; Mhd Arief Hasan (Universitas Islam Kuantan Singingi, 2021)
Pesantren is an educational institution that stands traditionally where students live in one place to live with each other and study under the guidance of a teacher who is also known as a Kiai. For its implementation, many things must be managed by a boarding school, starting from student registration, student placement, student learning, and evaluation of student learning at the boarding school. So far, there is no adequate system for all of these administrative needs. The purpose of this study is to build an information system framework for Islamic boarding schools using the TOGAF FRAMEWORK. Miftahul Huda Islamic Boarding School Pekanbaru City uses the TOGAF-ADM methodology as the standard tool used. The use of TOGAF can bring a consistent enterprise architecture, based on stakeholder requirements, and bring some considerations. . In designing this blueprint, it will rely on the work steps of the TOGAF ADM Framework, in which this enterprise architecture framework is divided into (four) categories, namely: business architecture, data, applications, and technology.